PENTINGNYA SOFT SKILLS TERHADAP PENGEMBANGAN KARIR MAHASISWA KE DEPAN - Imalinda Deryane (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
The purpose of this study is to examine the impact of soft skills on the future career of university students. Soft skills such as communication, public speaking, and leadership are crucial for success in the modern job market. The method used in this study is through a literature review by collecting library data, reading and taking notes, as well as gathering previous research to address the effect of soft skills on the future career of students. The study found that students with strong soft skills are more likely to have better job prospects, better salaries, and greater job satisfaction. The results of this research suggest that students should place a strong emphasis on developing their soft skills in order to enhance their future career opportunities